2019
DOI: 10.21425/f5fbg44577
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance dispersal in amphibians

Abstract: Highlights• This is the most complete and up-to-date review of long-distance dispersal (LDD) in amphibians, compiling information from more than 70 articles.• Although amphibians are considered poor to moderate dispersers, we show that they do perform LDD.• We propose that 10 km is a reasonable threshold for amphibian movements to be considered LDD.• The longest active LDD movement recovered in our bibliographic search was 34 km.• Passive overwater LDD events by means of rafting include movements of around 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Due to their risk of desiccation, open areas are often considered difficult for surface activity in these salamanders; however, studies of their migration in deforested areas as compared to their forested counterparts demonstrated no such limitation (Marsh et al., 2004). Additionally, studies exploring both past and contemporary patterns in range expansion suggest salamanders can disperse very long distances, though it varies among individuals and species (Fonte et al., 2019; Lowe, 2010; Pelletier & Carstens, 2016). We suspect that dispersal might be a strong predictor in how these species respond to climate change and that dispersal is not necessarily tied to habitat suitability because landscape features in relation to the resistance of gene flow have been found to vary across geographic areas within a single species of an eastern Plethodon salamander (Burgess & Garrick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their risk of desiccation, open areas are often considered difficult for surface activity in these salamanders; however, studies of their migration in deforested areas as compared to their forested counterparts demonstrated no such limitation (Marsh et al., 2004). Additionally, studies exploring both past and contemporary patterns in range expansion suggest salamanders can disperse very long distances, though it varies among individuals and species (Fonte et al., 2019; Lowe, 2010; Pelletier & Carstens, 2016). We suspect that dispersal might be a strong predictor in how these species respond to climate change and that dispersal is not necessarily tied to habitat suitability because landscape features in relation to the resistance of gene flow have been found to vary across geographic areas within a single species of an eastern Plethodon salamander (Burgess & Garrick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The large number of transatlantic dispersals discussed in the preceding paragraphs, including the case of Streblopus, are vivid examples of these new discoveries, and many further cases of dispersals across other oceans have been proposed (to mention just a few: Carranza et al 2000;Briggs 2003;Yoder & Nowak 2006;Kodandaramaiah & Wahlberg 2007;Miraldo et al 2011;Gillespie et al 2012;de Queiroz 2014;Mitchell et al 2014;Yonezawa et al 2017;Kodandaramaiah et al 2018;da Fonte et al 2019; and the literature cited therein). Contrary to the allegations of many vicariance biogeographers that allude to dispersal events is a leap of faith and therefore "unscientific", Gillespie et al (2012) have elegantly demonstrated how a sound knowledge of the physical and biological factors influencing the pace and direction of dispersal routes can help us to predict distributional patterns and understand why some groups have been able to colonize some lands whereas others have not.…”
Section: Discussionmentioning
confidence: 96%
“…Yet, most conjectures concerning the riverine barrier effect upon amphibians are based on their presumed weak ability to actively move across riverbanks, and little attention has been given to their potential ability to passively move across and along rivers. Since macrophyte rafts do represent an important medium of passive long‐distance dispersal for amphibians (Schiesari et al 2003, Fonte et al 2019), in some cases rivers can in fact facilitate dispersal instead of hampering it. If this is true, this effect should be stronger for typical floating meadows species and, as a consequence, they can be expected to have large geographic ranges across Amazonia.…”
Section: Discussionmentioning
confidence: 99%